Legal Origins and Female HIV - Anderson, Siwan (American Economic Review, 2018)
More than one-half of all people living with HIV are women and 80 percent of all HIV-positive women in the world live in sub- Saharan Africa. This paper demonstrates that the legal origins of these formerly colonized countries significantly determine current-day female HIV rates. In particular, female HIV rates are significantly higher in common law sub- Saharan African countries compared to civil law ones. This paper explains this relationship by focusing on differences in female property rights under the two codes of law. In sub- Saharan Africa, common law is associated with weaker female marital property laws. As a result, women in these common law countries have lower bargaining power within the household and are less able to negotiate safe sex practices and are thus more vulnerable to HIV, compared to their civil law counterparts. Exploiting the fact that some ethnic groups in sub- Saharan Africa cross country borders with different legal systems, we are able to include ethnicity fixed effects into a regression discontinuity approach. This allows us to control for a large set of cultural, geographical, and environmental factors that could be confounding the estimates. The results of this paper are consistent with gender inequality (the "feminization" of AIDS), explaining much of its prevalence in sub- Saharan Africa.